Higher education and migration - Mikaela Backman; Lina Bjerke (European Regional Science Association (ERSA), 2010)
We find that nearly 60 percent of the highly educated individuals in natural science, technology and manufacturing and health and medicine don't stay in their region of education and they have an average income that is higher than those that stay. In this paper we explore the relocation pattern of individuals assuming that they are heterogeneous in mobility and educational type. To the authors' knowledge there has not been any previous empirical research that distinguish between different categories of higher education and the factors influencing the probability to move can be divided into three. First, the income has a positive effect on the probability to move but plays only a minor role in the decision process compared to other decision factors. Second, the socio-biological factors such as age and gender are more significant in the decision process, which supports the results in earlier empirical studies. A third part of the decision process is the regional characteristics that create incentives to choose a geographical location corresponding to the individual preferences.
Keywords: R23; 330; labour mobility; highly educated individuals; inter-regional migration